Occurrence of Xyleborus bispinatus (Coleoptera: Curculionidae: Scolytinae) Eichhoff in southern Florida - Atkinson, Thomas H.; Carrillo, Daniel; Duncan, Rita E.; Peña, Jorge E. (Zootaxa, 2013)
Xyleborus bispinatus Eichhoff is reported from Florida for the first time. It was previously unrecognized and not distin-guished from Xyleborus ferrugineus (F.). There is no reason to believe at this point that it represents an introduction. Rather it is one of a group of widely distributed Neotropical species that are also found in southern Florida. Characters are discussed to allow it to be distinguished from X. ferrugineus and X. impressus Eichhoff.